Artificial intelligence in care: where does responsibility lie?. (2nd May 2019) - Stephenson, Jo; Acklam, Claire
Abstract : The problem of staff shortages in social care, paired with the developments in artificial intelligence technology, seems to point to a simple solution: implementing care robots. Jo Stephenson and Claire Acklam explore the legal implications of this.